2002
DOI: 10.1046/j.1472-765x.2002.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diversity of Paenibacillus polymyxa strains by using the DNA of bacteriophage IPy1 as a probe in hybridization experiments

Abstract: Aims: To evaluate the genetic diversity within the species Paenibacillus polymyxa. Methods: Southern hybridization was performed on 102 strains of P. polymyxa using DNA from the phage IPy1 as a probe. Results: All 102 strains hybridized to phage IPy1 DNA. Data from different hybridization patterns obtained were used to construct a dendrogram in which 53 genotypic groups were split into two main clusters. One cluster contained strains from the rhizospheres of sorghum and maize planted in Cerrado soil, Brazil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A few studies have documented the presence of a particular prophage in multiple isolates of the same bacterial species, using PCR and DNA hybridization, for example Paenibacillus polymyxa (Santos et al ., ), Salmonella enterica serovar Enteritidis (Agron et al ., ), and Streptococcus pneumoniae (Ramirez et al ., ). These reports concluded that the presence of prophage sequences in the bacterial genome had profound effects on host cell pathogenicity and population fitness.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have documented the presence of a particular prophage in multiple isolates of the same bacterial species, using PCR and DNA hybridization, for example Paenibacillus polymyxa (Santos et al ., ), Salmonella enterica serovar Enteritidis (Agron et al ., ), and Streptococcus pneumoniae (Ramirez et al ., ). These reports concluded that the presence of prophage sequences in the bacterial genome had profound effects on host cell pathogenicity and population fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Prophages are valuable tools for evaluation of the diversity and identification of bacterial strains. Such experiments were also performed on Paenibacillus species exploiting bacteriophages IPy1 (dos Santos et al , 2002) and PPL1c (Stahly et al , 1999). We decided to study another member of the group of bacteriophages from paenibacilli, the phage ΦBP, in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…These double stranded DNA phages are members of the Siphoviridae and Myoviridae families and, similar to the phages described by Francis & Rippon (1949), they were specific only to the strains of P. polymyxa . One of the bacteriophages – designated IPy1 (Seldin et al , 1984) – was recently used for evaluation of the genetic diversity within the species P. polymyxa (dos Santos et al , 2002). Phage IPy1 DNA served as a probe in hybridization studies.…”
Section: Introductionmentioning
confidence: 99%